Creatinine-based definitions: from baseline creatinine to serum creatinine adjustment in intensive care. Issue 1 (December 2016) - De Rosa, Silvia; Samoni, Sara; Ronco, Claudio
Abstract This article is one of ten reviews selected from the Annual Update in Intensive Care and Emergency medicine 2016. Other selected articles can be found online athttp://www.biomedcentral.com/collections/annualupdate2016 . Further information about the Annual Update in Intensive Care and Emergency Medicine is available fromhttp://www.springer.com/series/8901 .